2020
DOI: 10.1089/hs.2019.0122
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Risks Posed by the Convergence of Artificial Intelligence and Biotechnology

Abstract: Rapid developments are currently taking place in the fields of artificial intelligence (AI) and biotechnology, and applications arising from the convergence of these 2 fields are likely to offer immense opportunities that could greatly benefit human health and biosecurity. The combination of AI and biotechnology could potentially lead to breakthroughs in precision medicine, improved biosurveillance, and discovery of novel medical countermeasures as well as facilitate a more effective public health emergency re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…However, this line of research can raise questions about possible dual-use. O’Brien and Nelson ( 77 ) suggested that while the intended purpose of pathogenicity potential prediction is to mitigate biosecurity threats, it could actually enable designing new pathogens to cause maximal harm. The importance of this concern is difficult to overstate and it must be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…However, this line of research can raise questions about possible dual-use. O’Brien and Nelson ( 77 ) suggested that while the intended purpose of pathogenicity potential prediction is to mitigate biosecurity threats, it could actually enable designing new pathogens to cause maximal harm. The importance of this concern is difficult to overstate and it must be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…However, this line of research can raise questions about possible dual-use. O’Brien and Nelson (2020) suggested that while the intended purpose of pathogenicity potential prediction is to mitigate biosecurity threats, it could actually enable designing new pathogens to cause maximal harm. The importance of this concern is difficult to overstate and it must be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Technical details about the problems noted in AI software development, validation, and interpretability were not discussed. The risks of cyber attacks on AI systems, including ML vulnerability to adversarial attacks [ 190 , 191 ], and the difficulty in detecting and tracing software errors were not mentioned [ 165 ]. Approaches to select appropriate tasks for AI in medicine, enhance integration of AI tools into EHR and other connected hospital systems, improve data quality, or for ongoing safety monitoring were not discussed.…”
Section: Discussionmentioning
confidence: 99%